Formation of bis-benzimidazole and bis-benzoxazole through organocatalytic depolymerization of poly(ethylene terephthalate) and its mechanism. Issue 30 (4th June 2020) - Fukushima, Kazuki; Jones, Gavin O.; Horn, Hans W.; Rice, Julia E.; Kato, Takashi; Hedrick, James L.
Abstract : One-pot syntheses of bis-benzimidazole and bis-benzoxazole from poly(ethylene terephthalate) waste bottles were successful through two-step nucleophilic attacks promoted by TBD. Abstract : Environmental remediation through the recycling and upcycling of waste plastics is an urgent global concern. Accordingly, we herein demonstrate the organocatalyzed depolymerization of poly(ethylene terephthalate) (PET) with o -phenylenediamine (OPD) and 2-aminophenol (2AP) to form bis-benzimidazole and bis-benzoxazole, which can potentially be applied to the production of medicines, high-performance polymers, and organic electronics. Although high-temperature treatment at 190 °C was required, the neutral superbase 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) successfully facilitated two nucleophilic substitution reactions in one-pot, i.e., amidation or transesterification of PET followed by heterocycle formation to the amide or ester group. Theoretical studies with B3LYP density functional theory were performed for model reactions using methyl benzoate (MB) and OPD or 2AP. Consequently, we revealed that amidation favorably proceeds in the first depolymerization step and that the heterocycle formation predominantly results from nucleophilic attack to the amide intermediate by the anilinic NH2 or phenolic OH with the assistance of TBD. We also found that multiple hydrogen-bonding activations involving the bifunctional nature of TBD and the bidentate interactions of nucleophilic reagents such as OPD and 2AP with carbonyl oxygen atoms enable the one-pot formation of benzimidazoles and benzoxazoles from PET. Thus, this study not only demonstrates a new valuable method for upcycling of PET, but also offers a new synthetic route to benzimidazoles and benzoxazoles.